Silicon Valley, Women, and the California Dream: Gender, Class, and Opportunity in the Twentieth Century. - Gabaccia, Donna R. (American Historical Review, 2004)
Reviewed: Silicon Valley, Women, and the California Dream: Gender, Class, and Opportunity in the Twentieth Century. Matthews, Glenna.